Analysis of Visible Light Communication using Integrated Avalanche Photodiode - Ganji, Thriveni; Jetti, Vyshnavi; Manish, B. V. N Sai; Pogula, Srikanth Reddy; Rao, Y. Chalapathi (IRO Journal on Sustainable Wireless Systems, 2022)
The problem with Radio Frequency (RF) communication is that it has intrusion and high remission. Moreover, RF communication requires distinct configurations for transference and reception. To overcome these problems, Visible Light Communication (VLC) is recommended, as it has a high tolerance for bandwidth and interference. The usage of LEDs instead of fluorescent lamps uplifts the use of VLC. Visible light communication is a fast-evolving LED-based illumination and data transfer method. The performance of visible light communication over Mach-Zehnder Modulation has been investigated in this paper using the Opti-system simulation tool. The opti-system simulation programme predicts the quality factor and Bit Error Rate (BER) values of various link distances. The proposed system can handle 5 Gbps data rate over a 50-meter link distance with a Quality Factor of 15.71 and no external noise. The projected VLC system performance is further tested using a simulation tool in the case of external noise effects.